Advances and challenges of sand production and control in oilfields: A review - Muhammad Muhammad; Azad Anugerah Ali Rasol (Results in Engineering)
Sand production poses a critical issue in the oil and gas industry, particularly oil fields with unconsolidated sandstone reservoirs, resulting in equipment damage, wellbore instability, and heightened operational costs. The main causes of sand production include water breakthrough, unconsolidated formation, reduction in pore pressure, high production rate, gas to liquid ratio and phase change. Despite advancements in sand control methods, no single solution is universally effective for all reservoirs. Current technologies involve using advanced materials for screens, gravel packs, chemical treatment, different methods of sand prediction models, and emphasizing the integration of real-time monitoring systems to enhance sand control effectiveness. This paper discusses and analyzes the mechanisms of sand production, advanced sand management strategies, sand predictions model and monitory sensors, and challenges associated with sand control techniques, including mechanical, chemical methods, and hydrocyclone desanders. This paper highlighted some of the most used chemical agents in laboratory and field experiments for sand consolidation, are evaluated to determine their effectiveness in sand mitigation. Emphasis is placed on the limitations of existing chemical treatments and hydrocyclone desander, and the need for advanced chemical remediation techniques. Surface systems can be adjusted and maintained more easily than downhole sand control systems. Surface chemical treatment strategies such as introducing chemical sand coagulation-flocculation enhance hydrocyclone desander efficiency as new innovative sand control technology will serve as potential solutions for maintaining reservoir integrity and minimizing sand production.